Pengaruh Kualitas Sistem Informasi Akuntansi, Kecanggihan Teknologi Informasi, dan Kinerja Individual terhadap Efektivitas Sistem Informasi Akuntansi pada BPR Arta Bangsal Utama Mojokerto - Alful Alful laili; Tony Seno Aji (JFAS : Journal of Finance and Accounting Studies, 2021)
This study aims to determine the effect of the quality of accounting information systems, sophistication of information technology, and individual performance on the effectiveness of  accounting information systems at BPR Arta Bangsal Utama Mojokerto. The sampling techniqueyin this study used purposive sampling with a total of 40 respondents. The analysis technique used is the validity test technique, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing. The results of this study indicate that (1) the quality of the accounting information system has a significant effect on the effectiveness of the accounting information system which indicates that the higher the quality of the accounting information system, the more it affects the effectiveness of the accounting information system of BPR Arta Bangsal Utama Mojokerto. (2) the sophistication of information technology has alsignificant effect on the effectiveness of the accounting information system which shows that the higher the accounting information technology, the more it will affect the effectiveness of the accounting information system of BPR Arta Bangsal Utama Mojokerto. (3) individual performance has a significant effect on the effectiveness of the accounting information system, which indicates that the higher the individual performance, the more it affects the effectiveness of the accounting information system for BPR Arta Bangsal Mojokerto. Keywords: Quality of accounting information systems; Sophistication of accounting information technology, Individual performance; Effectiveness of accounting information systems.